(Re)constructing Indigenous Linguistic Refusal Beyond the Settler Gaze: Rebecca Belmore and Jalvvi Niillas Holmberg - Sutherland, Charlie (Scandinavian-Canadian Studies / Études scandinaves au Canada)

(untitled) (Association for the Advancement of Scandinavian Studies in Canada, 2025)
Indigenous art, aestheticisms, and other creative expressions represent a critical threat to settler colonial neoliberalism, working within, between, and beyond the parameters, definitions, and conventions of the Western art world. Using the concept of “Indigenous refusal” as a grounding framework, this article complicates the hegemonic relationship between settler fantasy and embodied Indigenous reality, exploring the ways that contemporary Indigenous artists Rebecca Belmore (Anishinaabe) and Jalvvi Niilas Holmberg (Sámi) foster Indigenous futurity through their artistic engagements with the presence and absence of language. Through a comparative analysis of Belmore’s 2013 performance piece Apparition and Holmberg’s second studio album, Luođik (2024), this paper argues that Belmore and Holmberg’s respective works map distinct geographies of refusal, exercising a sonic sovereignty in the service of disrupting the settler gaze. Building on previous decolonial scholarly work on the politics of refusal, reconciliation, and representation, this comparative approach makes obvious the thread of transnational Indigenous solidarity that links Belmore and Holmberg’s respective works together.